(untitled) (Journal of the College of Basic Education, 2022)
An experiment was conducted to study the effect of sowing dates on some yield traits of two cultivars of wheat, Triticum aestivumL. They are Ibaa 99 and Abu Ghraib. The two cultivars were planted on four dates: October 16, November 1, November 16, and December 1. The experiment was designed according to the randomized complete block design (R.C.B.D) with a split plot arrangement with three replications. The results of the study showed that The third date, November 16, had the highest rate of the number of spikes/m, the number of spikelets/spike, the number of grains per spike/spike, and the weight of 1000 grains (g), while the cultivars did not significantly affect these traits in the studied traits.